2020
DOI: 10.1159/000509026
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Course of Haemoglobin and Ferritin Values in High-Frequency Donors of Whole Blood and Double Erythrocyte Apheresis

Abstract: <b><i>Background:</i></b> High-intensity donation is a risk factor for iron deficiency in blood donors. Interdonation intervals for whole blood (WB) donation and double unit red blood cell apheresis (2RBC) vary among countries. We retrospectively evaluated the course of haemoglobin (Hb) and ferritin values in men regularly donating WB 4 times a year or 2RBC twice a year (i.e., maximal frequency) over a period of 48 months. <b><i>Methods:</i></b> Data of male dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…34 who donated more often tend to be older, which otherwise associates with higher ferritin levels, as shown in Figure 2 and previous research. 36,37 The large amount of data from many individual donors enabled us to not only compare ferritin levels from regular donors to nondonors, or from frequent to less-frequent donors, but to establish linear associations of donation numbers with (log-)ferritin levels in a real-life observational setting.…”
Section: Discussionmentioning
confidence: 99%
“…34 who donated more often tend to be older, which otherwise associates with higher ferritin levels, as shown in Figure 2 and previous research. 36,37 The large amount of data from many individual donors enabled us to not only compare ferritin levels from regular donors to nondonors, or from frequent to less-frequent donors, but to establish linear associations of donation numbers with (log-)ferritin levels in a real-life observational setting.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of iron depletion after blood donation is well known. One donation of two‐unit RBC is associated with an iron loss of roughly 320 to 420 mg 6,28,29 . Literature reports lots of donors delayed blood donation after 2 RBC due to iron deficiency 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…27 The phenomenon of iron depletion after blood donation is well known. One donation of two-unit RBC is associated with an iron loss of roughly 320 to 420 mg. 6,28,29 Literature reports lots of donors delayed blood donation after 2 RBC due to iron deficiency. 30,31 Sherman et al 10 reported that Hb was still significantly lower than baseline levels at 16 weeks after 2-RBC (400 mL) without iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of plasma donors found that iron deficiency was rare and not more common in high-frequency donors [26]. Recent findings indicating that with 24-week intervals between double red cell donations, young men maintain stable hemoglobin and ferritin over several years [27 ▪▪ ], which may be attributable to stringent minimum weight and hemoglobin eligibility criteria.…”
Section: Prevalence Of Iron Deficiency In Blood Donorsmentioning
confidence: 96%